Incidence of congenital syphilis according to inequalities and living conditions in the city of Recife, Pernambuco, Brazil - Roberta de Souza Pereira da Silva Ramos; Gledsângela Ribeiro Carneiro; André Luiz Sá de Oliveira; Tarcisio Neves da Cunha; Vânia Pinheiro Ramos (Instituto Materno Infantil de Pernambuco, 2021)
Abstract Objectives: to analyze the variation in the incidence rates of congenital syphilis according to the spatial distribution of Life Condition Index (LCI) among neighborhoods in the city of Recife-PE. Methods: an ecological study, developed from 3,234 cases of congenital syphilis notified in the Sistema de Informação de Agravos de Notificação (Severe Disease Notification Information System), between 2007 and 2016. LCI was built from seven variables related to the dimensions of the environment, education and income, aggregated at the neighborhood levels and spatially distributed in four strata: very high, high, low and very low. The correlation between the rates of congenital syphilis in the strata and LCI was investigated by applying the Spearman correlation coefficient and demonstrated by means of scatter graphics. Results: the mean rate on disease incidence was 6.8 cases per thousand live births. There was a higher incidence in the strata of very low and low living conditions, as well as in Districts that presented poor sanitary conditions and low schooling for the head of the family (District VII), higher proportion of illiteracy among 10 and 14 year olds (District II) and low income of the head of the household (Districts I, II and VII). Conclusions: this study showed the persistence of health inequalities in areas with worse living conditions.